Alcohol consumption and depressive symptoms as predictive factors of risk behaviors in urban transport drivers - Yana-Yana, Maribel Lizbeth (2024)
Background: In Peru, there are alarming statistics regarding traffic accidents caused by drivers under the influence of alcohol and emotional problems. Objective: This study aimed to identify whether alcohol consumption and depressive symptoms are predictors of the perception of risky behaviors in drivers. Method: The methodology followed a quantitative approach with a predictive scope, non-experimental design, and cross-sectional study. A non-probabilistic sample of 310 drivers aged 18 to 54 years was used, of whom 95% were male. The study utilized the Alcohol Use Disorders Identification Test (AUDIT), the Patient Health Questionnaire-9 (PHQ-9), and the Aversion to Risk Taking Scale to assess the participants. Results: Four out of 10 drivers exhibited depressive symptoms, and 7 out of 10 presented alcohol consumption issues. Regarding linear regression, an increase in alcohol consumption and depressive symptoms predicted 48.3% of the variance in the perception of risky driving behaviors. Conclusion: It is concluded that increased depressive symptoms and alcohol consumption are predictors of a decreased perception of risky driving behaviors. Future studies could implement interventions aimed at reducing risky behaviors by addressing depression and alcohol dependency in drivers.